A Nationally Representative Survey Assessing Restorative Sleep in US Adults - Robbins, Rebecca; Quan, Stuart F.; Buysse, Daniel J.; Weaver, Matthew D.; Walker, Matthew P.; Drake, Christopher L.; Monten, Kristen; Barger, Laura K.; Rajaratnam, Shantha M. W.; Roth, Thomas; Czeisler, Charles A. (Frontiers in Sleep, 2022)
Restorative sleep is a commonly used term but a poorly defined construct. Few studies have assessed restorative sleep in nationally representative samples. We convened a panel of 7 expert physicians and researchers to evaluate and enhance available measures of restorative sleep. We then developed the revised Restorative Sleep Questionnaire (REST-Q), which comprises 9 items assessing feelings resulting from the prior sleep episode, each with 5-point Likert response scales. Finally, we assessed the prevalence of high, somewhat, and low REST-Q scores in a nationally representative sample of US adults (n = 1,055) and examined the relationship of REST-Q scores with other sleep and demographic characteristics. Pairwise correlations were performed between the REST-Q scores and other self-reported sleep measures. Weighted logistic regression analyses were conducted to compare scores on the REST-Q with demographic variables. The prevalence of higher REST-Q scores (4 or 5 on the Likert scale) was 28.1% in the nationally representative sample. REST-Q scores positively correlated with sleep quality (r = 0.61) and sleep duration (r = 0.32), and negatively correlated with both difficulty falling asleep (r = −0.40) and falling back asleep after waking (r = −0.41). Higher restorative sleep scores (indicating more feelings of restoration upon waking) were more common among those who were: ≥60 years of age (OR = 4.20, 95% CI: 1.92–9.17); widowed (OR = 2.35, 95% CI: 1.01–5.42), and retired (OR = 2.02, 95% CI: 1.30–3.14). Higher restorative sleep scores were less frequent among those who were not working “other” (e.g., a person performing household duties, OR = 0.36, 95% CI: 0.10–1.00) and living in a household with two or more persons (OR = 0.51, 95% CI: 0.29–0.87). Our findings suggest that the REST-Q may be useful for assessing restorative sleep.